Phytochemical Analysis, α-glucosidase Inhibition Activity in-vitro and Enzyme Kinetics of Ethyl Acetate and Hexane Extracts of Graptophylum pictum (L.) Griff - Waras Nurcholis; I Made Artika; Djarot Sasongko Hami Seno; Dimas Andrianto; Apipah Aprianti; Fina Febrianti; Inawati Inawati; Antonius Padua Ratu; Arya Arendra (Current Biochemistry, 2014)
The species Graptophylum pictum (L.) Griff, also known as “daun ungu” in Indonesia, is a traditional herbaceous plant believed to have antidiabetic potential. The number of people in the world with diabetes has increased dramatically over the recent years. The treatment of type II diabetes is complicated by several factors inherent to the disease. Elevated postprandial hyperglycemia is one of the risk factors and the intestinal digestive enzyme α-glucosidase plays a vital role in carbohydrate metabolism. One of the antidiabetic therapeutic approaches which reduces the postprandial glucose level in blood is by the inhibition of α-glucosidase. In this study, phytochemical analysis, α- glucosidase inhibitory activity and enzyme kinetics of ethyl acetate- and hexane extracts of G. pictum were evaluated with the aim to analyze its antidiabetic potential. Phytochemical analysis revealed the presence of tannins, steroids, and alkaloids. Steroids were present in ethyl acetate extract but absent in hexane extract, while alkaloids were present in hexane extract but absent in ethyl acetate extract. The ethyl acetate and hexane extracts had 30.68 and 49.82 % inhibitory effect on α-glucosidase activity respectively. The kinetics of glucosidase enzyme of ethyl acetate and hexane extracts were determined by Lineweaver Burk plots. These exhibited uncompetitive and noncompetitive inhibition to alpha-glucosidase activity respectively. From the enzyme assay, we infer that ethyl acetate and hexane extracts of G. pictum contain potential α-glucosidase inhibitors that have the potential to be exploited for use in the treatment of diabetes